Analisis Swot Terhadap Pengetahuan Wakaf Uang Masyarakat Desa Banaran Kecamatan Geger - Ayatusyifaq, Annafi; Muhtadin Amri (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2024)
The people of Banaran Village, Geger District, Madiun Regency have long been familiar with the practice of cash waqf. Instead of following waqf innovation to advance villages to become more productive. The people of Banaran Village, Geger District, Madiun Regency prefer to use waqf funds for the construction or renovation of buildings around the village. This is motivated by the lack of public knowledge regarding cash waqf innovation. This research aims to determine the strengths, weaknesses, opportunities and threats that exist in Banaran Village, Geger District, Madiun Regency. And SWOT analysis in Banaran Village. This research uses field research with a descriptive qualitative approach. The research results show that the knowledge of the people of Banaran Village, Geger Madiun District is still limited to the concept of cash waqf. Most people understand that cash waqf is used only for development. Even though this village has large potential for waqf funds, productive waqf innovations for the welfare of the people have not been implemented. The results of the SWOT analysis show the results of quadrant 4. This has positive value to be utilized by Banaran Village for the progress of the village